ANALYSIS OF ULTRASOUND EXAMINATION WITH HISTOPATHOLOGICAL READINGS IN BREAST CANCER PATIENTS AT PROF. DR. CHAIRUDDIN P. LUBIS HOSPITAL USU MEDAN - Hafiz Nurdiansyah; Liandra Khairunnisa; Elvita Rahmi Daulay; Endi Taris Pasaribu (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Breast cancer is the type of cancer with the highest prevalence in women and is the leading cause of cancer death globally. Early detection is very important to determine the right management, one of which is through ultrasound examination (ultrasound) as a non-invasive imaging method. However, the validity of ultrasound results still needs to be studied through comparison with histopathological results as the gold standard of diagnosis. This study aims to analyze the suitability between the results of ultrasound examination and the results of histopathological readings in breast cancer patients at Prof. Dr. Chairuddin P. Lubis Hospital USU Medan. The study used a cross-sectional design of 48 patients who underwent ultrasound and histopathological examinations throughout 2023. The results showed that 29 patients were classified as having malignant tumors based on ultrasound, but only 26 were confirmed malignant through histopathology. The compatibility rate between the two methods was only 37.5%, and the Fisher Exact test showed no statistically significant compatibility (p < 0.01). These findings suggest that ultrasound examination has limitations in distinguishing benign and malignant lesions. Therefore, ultrasound results need to be confirmed by histopathological examination to avoid misdiagnosis and therapy. This study confirms the importance of a multimodal approach in breast cancer diagnosis.